Changes in lipoproteins associated with lipid-lowering and antiplatelet strategies in patients with acute myocardial infarction. - Zahra Lotfollahi; Ana P Q Mello; Francisco A H Fonseca; Luciene O Machado; Andressa F Mathias; Maria C Izar; Nagila R T Damasceno; Cristiano L P Oliveira; Antônio M F Neto (PLoS ONE)
Background Despite lipid-lowering and antiplatelet therapy, the pattern of residual lipoproteins seems relevant to long-term cardiovascular outcomes. This study aims to evaluate the effects of combined therapies, commonly used in subjects with acute myocardial infarction, in the quality of low-density lipoprotein (LDL) particles. Methods Prospective, open-label trial, included patients with acute myocardial infarction. Patients were randomized to antiplatelet treatment (ticagrelor or clopidogrel) and subsequently to lipid-lowering therapy (rosuvastatin or simvastatin/ezetimibe) and were followed up for six months. Nonlinear optical properties of LDL samples were examined by Gaussian laser beam (Z-scan) to verify the oxidative state of these lipoproteins, small angle X-ray scattering (SAXS) to analyze structural changes on these particles, dynamic light scattering (DLS) to estimate the particle size distribution, ultra violet (UV)-visible spectroscopy to evaluate the absorbance at wavelength 484 nm (typical from carotenoids), and polyacrylamide gel electrophoresis (Lipoprint) to analyze the LDL subfractions. Results Simvastatin/ezetimibe with either clopidogrel or ticagrelor was associated with less oxidized LDL, and simvastatin/ezetimibe with ticagrelor to lower cholesterol content in the atherogenic subfractions of LDL, while rosuvastatin with ticagrelor was the only combination associated with increase in LDL size. Conclusions The quality of LDL particles was influenced by the antiplatelet/lipid-lowering strategy, with ticagrelor being associated with the best performance with both lipid-lowering therapies. Trial registration: NCT02428374.